2017
DOI: 10.4102/safp.v59i3.4538
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety symptoms and substance use amongst sex workers attending a non-governmental organisation in KwaZulu-Natal, South Africa

Abstract: Background: Sex work is a high-risk occupation for mental health problems as sex workers are vulnerable to high rates of violence, sexual coercion, stigma and HIV. Aim: To determine the prevalence of depressive and anxiety symptoms and substance use in sex workers.Method: A crosssectional questionnaire survey of all men and women attending the Sisonke health initiative, a non-profit non-governmental organisation (NGO), for sex workers was conducted over three months. A socio-demographic questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…In addition to alcohol, studies have shown a high prevalence of substance use (alcohol and other drug use) amongst sex workers, both globally and in South Africa [9,10]. A 2015 study of FSWs in KwaZulu-Natal found that 83.2% of respondents admitted to lifetime substance use [11]. Across the country, the use of opioids such as heroin, codeine, and Nyaope (antiretroviral therapy [ART] medication mixed with detergent, rat poison, marijuana, and/or methamphetamine) has been increasing [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to alcohol, studies have shown a high prevalence of substance use (alcohol and other drug use) amongst sex workers, both globally and in South Africa [9,10]. A 2015 study of FSWs in KwaZulu-Natal found that 83.2% of respondents admitted to lifetime substance use [11]. Across the country, the use of opioids such as heroin, codeine, and Nyaope (antiretroviral therapy [ART] medication mixed with detergent, rat poison, marijuana, and/or methamphetamine) has been increasing [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Almost 86.6% of FSWs reported experiencing some form of violence in their lifetime [25]. The increased prevalence of substance use that FSWs face may account for the higher prevalence of mental health issues compared to the general population [11]. Findings from previous research highlight a high prevalence of depressive symptoms amongst FSWs, with more than two thirds of FSWs in Soweto experiencing symptoms suggestive of severe depression, and more than a third suggestive of post-traumatic stress disorder (PTSD) [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the global literature different anxiety and depression prevalence rates were reported among FSWs where some were higher, others comparable and some others were lower than the rate found in our study. For instance, the rates of depression levels range from 9% among FSWs in China (Tam et al, 2022) to 80.9% among FSWs in South Africa (5).…”
Section: Discussionmentioning
confidence: 99%
“…Due to a dearth of study on relevant services which focused on the needs and aspirations of CSWs, the number of CSWs continues to rise over the world, owing to the high frequency of violence and the resulting reproductive and mental health difficulties (Poliah and Paruk, 2017;Wong, 2009). According to World Health Organization (2018), over 376 million new infections among CSWs and more than 1 million Sexually Transmitted Infections (STIs) occurring each day globally.…”
Section: Introductionmentioning
confidence: 99%